2017
DOI: 10.1111/jfpp.13491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spray drying compartment and maltodextrin concentration on the functional, physical, thermal, and nutritional characteristics of Bambara groundnut milk powder

Abstract: The study examined the effect of drying compartment and maltodextrin concentration on the functional properties of Bambara groundnut milk powder (BGNMP). Bambara groundnut milk (BGNM) was prepared from Bambara groundnut (BGN) flour and water, further processed into BGNM and dried using the spray drying process. Total solids of BGNM were increased with 5, 10, and 15% of maltodextrin. Functional properties of BGNMP were analyzed. Water absorption indices (WAI), wettability, and water solubility indices (WSI) ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
(75 reference statements)
2
8
0
Order By: Relevance
“…The average protein content of fermented whey dangke powder was 12.04%, indicating an increase compared with the liquid product, which was 2.34%. The same thing was reported by Hardy and Jideani (2018) stating that the protein content of Bogor soy milk flour is higher than that of Bogor soy milk i.e. 0.9% to 7.6%.…”
Section: Protein Contentsupporting
confidence: 76%
“…The average protein content of fermented whey dangke powder was 12.04%, indicating an increase compared with the liquid product, which was 2.34%. The same thing was reported by Hardy and Jideani (2018) stating that the protein content of Bogor soy milk flour is higher than that of Bogor soy milk i.e. 0.9% to 7.6%.…”
Section: Protein Contentsupporting
confidence: 76%
“…Examples of such milk include milk from plant or vegetable sources such as those extracted from soybean or bambara groundnut. Hardy and Jideani (2017) reported that bambara groundnut has prospects in improving food security through shelf-stable food products, which could be produced from it. They produced protein-rich bambara groundnut milk powder from bambara groundnut flour and water through spray drying of bambara groundnut milk.…”
Section: Use Of Bambara Groundnut In Milk and Yogurt Productionmentioning
confidence: 99%
“…Bambara groundnut milk powder (BGNMP) was produced using method by Hardy & Jideani (2017). The TS of BGN milk as described in Section 2.2 was adjusted to 10% using corn maltodextrin (20 dextrose equivalent) as a drying carrier.…”
Section: Spray Drying Of the Bambara Groundnut Milkmentioning
confidence: 99%
“…Meanwhile, the viable starter counts of foam-mat dried BGNPY-R and BGNPY-NR were observed to be 7.20 and 5.22 log cfu/ml, respectively. TA B L E 3 Particle size, particle size distribution, and color characteristics of BGNPY-R and BGNPY-NR Hardy & Jideani (2017). BGNMP contained a denser nutrient profile (protein: 7.6%, total fat: 1.6%, carbohydrate: 72.4), in comparison with that of BGNM (protein: 0.9%, total fat: 0.3%, carbohydrate:…”
Section: Microbial Load Characteristics Of Bambara Groundnut Powdermentioning
confidence: 99%